If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 21 + -6x = 9 + -9x Solving 21 + -6x = 9 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 21 + -6x + 9x = 9 + -9x + 9x Combine like terms: -6x + 9x = 3x 21 + 3x = 9 + -9x + 9x Combine like terms: -9x + 9x = 0 21 + 3x = 9 + 0 21 + 3x = 9 Add '-21' to each side of the equation. 21 + -21 + 3x = 9 + -21 Combine like terms: 21 + -21 = 0 0 + 3x = 9 + -21 3x = 9 + -21 Combine like terms: 9 + -21 = -12 3x = -12 Divide each side by '3'. x = -4 Simplifying x = -4
| tn=tn-1+2 | | x+4=0.5(2x-7) | | 5q+p=q-3 | | 3(7x+9)=48 | | x^2+y^2=1600 | | 7*[3(3)-2]+5=6*[2(3)-1]+24 | | 2cos^2-5cos-3=0 | | 6=-3+33 | | k-15=-30 | | tn=3n-1 | | 9+4x=23 | | 4X+11=2X^2+13X+6 | | -7(-6x+2)=48 | | 5(x+11)=5(12-x) | | 4x+9=-31-4x | | e-6=7 | | tn=tn-1-4 | | 4(-7+2x)=-28 | | 3(3-y)1=31 | | -4x^3+4x^2+35x=0 | | 2-a=3 | | 4x-23x+18x-278=34 | | x^2-1040x=0 | | 7[3(3)-2]+5=6[2(3)-1]+24 | | 44x-23+18x-278=34 | | m+8=-10 | | X-(-x-2)=-8 | | 44x-23+18x-278=345 | | 3x-5=-12x-59 | | tn=4n+3 | | 11x-6=7x+7 | | (3x+6)(x+7)=0 |